Implementasi Metode Entropy dan Technique For Order Preference by Similarity to Ideal Solution (TOPSIS) dalam Pemilihan Biro Perjalanan Umroh - Meiriza, Allsela; Ruskan, Endang Lestari; Zulfahmi, Rido (Teknomatika, 2019)
Abstract Increased desire of Muslims in performing Umrah, sometimes making prospective pilgrims not selective in choosing a trusted umrah travel agency, consequently it causes regret and loss for prospective worshipers, besides that there is an alternative choice of various Umrah travel agencies, it takes time in determining a trusted Umrah travel agency. Therefore, information is needed that is fast and up to date, and able to provide recommendations in supporting the decisions of prospective pilgrims to determine the choice of a trusted Umrah travel agency. This study uses the Entropy and Technique For Order Preference By Similarity To Ideal Solution (TOPSIS) method in generating ranking. The criteria used in this election are service, security, facilities, existence, price, travel package, trust. Data from the Umrah travel agency were obtained from the Ministry of Religion (Kemenag) of Palembang City. The final results of this study are in the form of recommendations for the Umrah religious umrah travel agency in the form of website-based ranking. Keywords-Decision Support System, Entropy, TOPSIS, Umrah Travel Agency